Characterizing Micro-scale Disparities in Childhood Obesity: Examining the Influence of Multilevel Factors on 4-Year Changes in BMI, Healthy Eating, and Physical Activity, Among a Cohort of Children Residing in Disadvantaged Urban Enclaves - Salvo, Deborah; Ranjit, Nalini; Nielsen, Aida; Akhavan, Nika; van den Berg, Alexandra (Frontiers in Public Health, 2019)
The childhood obesity epidemic in the United States disproportionately affects minority, low-income populations. Hispanics have one of the highest childhood obesity rates, and are the fastest growing population subgroup in the country. Past research has examined disparities in the occurrence of obesity, healthy eating, and physical activity at a macro-geographic level, with less emphasis on examining the multilevel, micro-scale determinants of childhood obesity in disadvantaged urban ethnic enclaves. The aim of our study was to identify child-, parental-, familial-, community-, and neighborhood-level factors associated with differences in 4-year changes in BMI, healthy eating, and physical activity, among children residing in low-income, predominantly Hispanic urban enclaves in Austin, Texas. This analysis used data from the Go Austin! Vamos Austin! (GAVA) Evaluation study, a cohort with 4 years of follow-up from 313 child-caregiver dyads. The dependent variables were change categories denoting 4-year increase, decrease, or no change in Body Mass Index (BMI) percentile, fruit and vegetable intake, and physical activity, among child participants. The independent variables were factors at multiple levels of the socio-ecological model: child, parental, familial, community, and environmental. Multinomial logistic regression models were used to estimate the odds of children being in the “increasing” or “decreasing” categories for the three dependent variables (vs. “no change”), in association with the studied independent variables. The results showed that among children residing in this low-income, predominantly Hispanic urban enclave, weight gain prevention and weight loss have different determinants. We identified relevant micro-scale disparities, and micro-level factors of influence on child BMI and its related health behaviors, at all levels of the socio-ecological model. Our results revealed evidence, through the characterization of positive deviance cases (children for whom decreases in BMI, increases in fruit and vegetable intake, or increases in physical activity were observed) which could potentially help mitigate established unhealthy habits among high need populations. Factors associated with positive deviance for BMI (decreases in child BMI) included male child sex (OR: 0.33, 95%CI: 0.12-0.83) and living in a food-insecure household (OR: 0.24, 95%CI: 0.13-0.79). Our findings may inform the design of obesity prevention interventions in these types of disadvantaged urban Hispanic enclaves.